097 Calcium scores are more cost effective for risk stratification than NICE's modified diamond Forrester calculator. (16th May 2012) - McCusker, S; McKavanagh, P; Lusk, L; Agus, A; Ball, P; Harbinson, M; Trinnick, T; Duly, E; Walls, G; Shevlin, S; McQuillan, C L; Alkhalil, M; et al.
Abstract : Background: In March 2010 NICE published clinical guideline 95 (CG95). This proposed a move to a primary imaging strategy for investigation of stable chest pain. CG95 uses a modified Diamond Forrester (DF) to evaluate individuals' risk of coronary artery disease (CAD) and determine the most appropriate test. Patients with DF likelihood scores <10% do not require further investigation; 10%–29% require calcium scores (CS); 30%–60% stress imaging; and >60% invasive angiography (IA). For those patients requiring CS, the guidance recommends that a score of 0 requires no further investigation; 1–399 CT angiogram (CTCA); and >400 IA. This study compared the cost implications of DF and CS as risk stratification tools as part of a larger ongoing randomised control trial, CAPP (Cardiac CT for the Assessment of Chest Pain and Plaque) [ISRCTN52480460 ], which aims to evaluate the cost-effectiveness of cardiac CT. Methods: Written and informed consent was obtained from 250 patients with stable chest pain. Age, sex, risk factors and character of pain were documented, and the probability of significant CAD was calculated using the DF. Patients had CS followed by CTCA, performed on a Philips Brilliance 64. CS was assessed using a semi-automated analysis package to determine the Agatston score. CTCA was taken as the reference point for CAD severity, with disease classified according to the most significant lesion, ranging from none to severe. The total number and cost for investigations was determined theoretically by two models. Model 1 used the DF and model 2 the CS criteria. The unit costs of the investigations were obtained from the NHS National Tariff 2011/12 and NICE CG95. Results: Of the 250 patients three withdrew. 146 of the 247 were male with a mean age of 57.93. The mean CS was 175.84. The average DF was 48.21%. CS predicted CAD better than DF score (McNemar's χ 2 =14.52, p<0.0001). OR=2.88 (95% CI 1.60 to 5.44). When the cost implementation of CG95 was assessed using the DF criteria, 52 had scores between 0–9 and no further investigation was needed; 49 between 10% and 29% required CS; 53 between 30% and 60%, needed stress imaging; and 93 above 61% required IA. Of the 49 that would receive CS, 28 had a score of 0 requiring no further investigations; 17 had a CS>0–400 necessitating CTCA; 4 had a CS above 400 and required IA. This model had a projected total cost of £124 130. When the cost implementation of CG95 was assessed using the CS, the cost for investigation would be 247 CS; 126 patients had a CS of 0 and no further investigation was necessary; 94 had a CS>0–400 and CTCA is indicated; and 27 had a CS above 400 and would require IA. This model had a projected total cost of £48 282. Conclusions: The use of CS to triage patients with stable chest pain appears to be more cost effective for the prediction of CAD. This model could replace the subjective and difficult assessment of chest pain symptoms with a more objective assessment of CAD presence.